Upaya Pembentukan Kecerdasan Spiritual Santri di Pondok Pesantren Mafatihussalam Sidoharjo Lampung Selatan - Mas Ayu Intan; Muhammad Feri Fernadi; Eka Tusyana (Journal on Education, 2023)
This review expects to decide the Endeavors to Frame the Otherworldly Insight of Santri at the Mafatihussalam Jati Agung Islamic All inclusive School, South Lampung. This study utilizes a clear distinct strategy, with the kind of examination covering contextual investigations, with information assortment through meetings, perception and documentation. The outcomes showed that endeavors to shape the otherworldly knowledge of understudies at the Mafatihussalam Islamic Live-in School, Sidoharjo Town, Jati Agung Area, South Lampung Regime comprised of three action meetings. In particular: a. Endeavors to frame the profound knowledge of the Santri did by the Mafatihussalam Islamic Life experience School are: Recognition of Manakib and Practice of Asmaul Husna. b. Deterrents in the development of profound knowledge, to be specific: Low mindfulness, Family Climate and Relationship of Friends.c. The positive effect on the development of otherworldly knowledge at the Mafatihussalam Islamic Live-in School is: in the discipline of rehearsing religion, dutifulness to guardians is helpful for being capable.